Prevalence of Alloantibodies in Thalassemia Patients and Its Relationship With Age, Gender and Blood Group - Leili Koochakzadeh; Mohammad Kajiyazdi; Fahimeh Khoshhal; Alireza Hashemi; Mehdi Khabazkhoob (Acta Medica Iranica, 2023)
To determine the prevalence of alloantibodies in patients with thalassemia and its relationship with age, sex, and blood group. A cross-sectional study was conducted on thalassemia patients requiring a blood transfusion presenting to Children’s Medical Center and Bahmari Hospital in 2021. All patients who received blood transfusions in the first year of life were included in the study, and patients with sickle cell anemia and thalassemia intermedia were excluded. Blood samples were collected, and the level of alloantibodies was measured. One hundred and ninety-five patients were evaluated in this study, of whom 100 (51.3%) were male. The mean age of the subjects was 21.37±8.57 years (range: 1-42 years). The prevalence of alloantibody positivity was 16.41% (11.17-21.65) in all subjects, 19% (11.18-26.82) in males, and 13.68% (6.65-20.72) in females (P=0.318). The mean age of alloantibody positive and negative subjects was 18.94±9.7 and 21.85±8.29 years, respectively (P=0.079). The prevalence of alloantibody positivity was 21.88% (6.73-37.02) in Rh+ and 15.34% (9.75-20.93) in Rh- patients (P=0.364). The prevalence of alloantibody positivity was 13.46% (3.87-23.06) in blood type A, 26.67% (1.32-52.02) in blood type AB, 14.29% (3.25-25.32) in blood type B, and 17.44% (9.26-25.63) in blood type O, indicating no significant difference in this regard (P=0.625). The results showed that thalassemia patients were at risk for alloantibody positivity. Age, sex, and blood type had no significant association with the prevalence of alloantibody positivity. Considering the serious complications of these antibodies, these patients should be continuously screened for the presence of alloantibodies.